COMPARATIVE EVALUATION OF PERMANENT CARDIAC PACING IN PACEMAKER-DEPENDENT PATIENTS WITH DIFFERENT PATTERNS OF RIGHT VENTRICLE EXCITATION - V. V. Korshunov; G. V. Chudinov; V. P. Terentiev (Медицинский вестник Юга России, 2015)
Purpose: comparative analysis of the effectiveness of permanent cardiac pacing and quality of life in the pacemaker-dependent chronical heart failure patients with different patterns of excitation of the right ventricle.Materials and methods: we examined 108 patients with hemodynamically significant atrioventricular conduction disturbances and chronical heart failure who underwent permanent pacemaker implantation. All patients were divided into 2 groups depending on performed right ventricle pacing site.Results: in assessing the electrocardiogram have been improvements in the dynamics of the QRS morphology in patients with alternative para-Hisian site pacing. It was established that the interventricular mechanical delay in patients of the apical group pacing was significantly higher compared with an alternative stimulation patients group. Revealed relatively low exercise tolerance, as well as the lowest values of the physical component of patients health in the apical pacing group.Summary: the permanent para-Hisian pacing in patients with chronical heart failure can be obtained normal morphology of the QRS complex with reduced ventricular dyssynchrony. Is the preferred alternative method to the apical pacing .